Psychoeducational Interventions for Family Caregivers of Seniors across Their Life Trajectory: An Evidence-Based Research Program to Inform Clinical Practice. (19th June 2014) - Ducharme, Francine
Abstract : Family caregivers of the elderly are growing in number and the care they are called upon to deliver in industrialized countries is becoming increasingly demanding and complex. Empirical research shows that the caregiving situation can have a significant impact on the health of these caregivers often on account of stress, physical and psychological exhaustion, and a sense of being overwhelmed. In this context, the quality of life of these caregivers depends in large part on professional educational and support interventions. The purpose of this paper is to present three innovative psychoeducational intervention programs developed and empirically tested by the research team of the Université de Montréal's (Québec, Canada) Chair in Nursing Care for Seniors and Their Families over the past fifteen years. These interventions have been developed together with family caregivers experiencing different stressful situations across their care trajectory. The results of evaluative studies of these programs provide evidence to inform professional clinical practice. Future directions for caregiving research are discussed.